2004
DOI: 10.1002/mc.20045
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA microarray analyses to elucidate the effects of genistein in androgen‐responsive prostate cancer cells: Identification of novel targets

Abstract: Many studies have correlated the consumption of soy-rich diets with a decreased risk of developing hormone-dependent cancers, including prostate cancer. Genistein is a candidate prostate cancer preventive phytochemical found at high levels in soybean and soy foods. To better understand the molecular mechanisms underlying the beneficial effects of genistein on prostate cancer prevention, we used a DNA microarray approach to examine the effects of genistein at concentrations in the physiologic range on global ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 48 publications
9
56
1
Order By: Relevance
“…Cluster analyses (35) revealed that genistein regulates the expression of genes that are critically involved in the regulation of apoptosis, cell cycle, cellular signaling, angiogenesis, invasion, and metastasis. A similar pleiotropic action of genistein on multiple signaling pathways was observed when cDNA microarray studies were conducted using LNCaP cells (36).…”
Section: Effect On Invasion and Metastasismentioning
confidence: 75%
“…Cluster analyses (35) revealed that genistein regulates the expression of genes that are critically involved in the regulation of apoptosis, cell cycle, cellular signaling, angiogenesis, invasion, and metastasis. A similar pleiotropic action of genistein on multiple signaling pathways was observed when cDNA microarray studies were conducted using LNCaP cells (36).…”
Section: Effect On Invasion and Metastasismentioning
confidence: 75%
“…In contrast, in vitro studies using androgen-responsive prostate cancer cells showed that genistein, daidzein, and equol all consistently inhibit IGF-IR mRNA expression, even at relatively low levels of exposure (i.e., being comparable to human dietary intake; refs. 43,44). In cultured HT-29 human colon cancer cells, genistein, but not daidzein, was found to reduce IGF-IR protein levels and inhibit IGF-IR signaling at relatively high pharmacologic concentrations (45).…”
Section: Discussionmentioning
confidence: 93%
“…For example, they are strong antioxidants [2,3], inhibit tumor formation [4], improve endothelial function [5,6] and affect energy metabolism [7]. To elucidate the molecular mechanisms explaining the beneficial effects of flavonoids observed in vivo, several studies have employed a systems biology approach with transcriptomics and proteomics techniques, using cell culture systems [8][9][10][11][12][13][14][15][16][17][18]. However, these in vitro studies may have generated misleading findings due to the non-physiological exposure conditions mostly used.…”
Section: Introductionmentioning
confidence: 99%